Thermal Modeling, Exergy Analysis, Performance of BIPV and BIPVT: A Review - Debbarmaa, Mary; Sudhakar, K.; Baredar, Prashant (Elsevier, 2017)
People are becoming more and more sensitive to the ecological consequences of global warming and environmental devastation. The objective is to replace the use of fossil fuel energy with renewable forms of energy. In the field of building construction, this leads to a new legislation frameworks and radical changes in how we design our buildings. The use of renewable in the building envelope is much varied and opens many opportunities for creative designers. Many architects have already integrated PV successfully in their buildings. This paper reviews the present day application of BIPV and BIPV-T technologies. In addition to it thermal modeling, energy and exergy analysis of BIPV and BIPVT system are also discussed. This study also reviews the recent developments of the technology worldwide.